Evaluasi Program Zero Waste dalam Mencapai Pengurangan Limbah Secara Berkelanjutan di SMAN 4 Mataram - Hurriyah, Daeng Siti; Saputra, Heri Hadi (Universitas Negeri Malang, 2024)
Abstract: This study evaluates the effectiveness of the zero waste program at SMAN 4 Mataram in promoting sustainable waste reduction. Using a descriptive qualitative approach with evaluative methods, the research aims to assess the extent to which the Zero Waste program achieves its objectives in raising environmental awareness and waste management practices within the school environment. Data were collected through interviews, observations, and documentation from various stakeholders, including students, teachers, custodial staff, and program managers. The findings indicate that the program has successfully increased awareness and participation among the school community regarding the importance of waste management. Most students and teachers actively participate in sorting organic and inorganic waste, as well as in composting activities. However, there are some challenges in implementation, such as limited recycling facilities and a lack of regular supervision, which affect the program's optimization. Additionally, not all students demonstrate full awareness and engagement in the program, with instances of littering still observed. This study recommends improving supporting facilities, providing continuous training for students, and conducting regular monitoring and evaluation to strengthen program implementation. With improvements in these areas, the zero waste program at SMAN 4 Mataram is expected to achieve more optimal results and significantly contribute to fostering sustainable environmental awareness within the school. Keywords: Zero Waste, waste reduction, program evaluation, environmental awareness, school Abstrak: Penelitian ini mengevaluasi efektivitas program zero waste di SMAN 4 Mataram dalam rangka pengurangan limbah secara berkelanjutan. Menggunakan pendekatan kualitatif deskriptif dengan metode evaluatif, penelitian ini bertujuan untuk memahami sejauh mana program zero waste mencapai tujuannya dalam meningkatkan kesadaran lingkungan dan pengelolaan limbah di lingkungan sekolah. Data diperoleh melalui wawancara, observasi, dan dokumentasi dari berbagai pemangku kepentingan, termasuk siswa, guru, staf kebersihan, dan pengelola program. Hasil penelitian menunjukkan bahwa program ini berhasil meningkatkan kesadaran dan partisipasi warga sekolah terhadap pentingnya pengelolaan limbah. Sebagian besar siswa dan guru terlibat aktif dalam pemilahan sampah organik dan anorganik, serta dalam kegiatan kompos. Namun, terdapat beberapa kendala dalam implementasi, seperti minimnya fasilitas daur ulang dan kurangnya pengawasan berkala, yang berdampak pada optimalisasi program. Selain itu, belum seluruh siswa memiliki kesadaran dan keterlibatan penuh dalam program, sehingga perilaku pembuangan sampah sembarangan masih ditemukan. Penelitian ini merekomendasikan peningkatan fasilitas pendukung, pelatihan berkelanjutan untuk siswa, serta monitoring dan evaluasi berkala untuk memperkuat implementasi program. Dengan peningkatan pada aspek-aspek tersebut, diharapkan program zero waste di SMAN 4 Mataram dapat mencapai hasil yang lebih optimal dan memberikan kontribusi yang signifikan terhadap pembentukan kesadaran lingkungan yang berkelanjutan di sekolah. Kata Kunci: Zero Waste, pengurangan limbah, evaluasi program, kesadaran lingkungan, sekolah